IMPROVING ATTENTION CHARACTERISTICS IN CHILDREN WITH DYSARTHRIC SPEECH DISORDERS - Iminjonova Mokhichehra Alimardon qizi (GLOBAL SCIENTIFIC RESEARCH AND INTELLECTUAL PURSUITS, 2026)
This article explores the psychological characteristics of the attention process in children with dysarthria, factors leading to its decline, and effective methods for developing attention. Dysarthria significantly affects not only the function of the articulatory apparatus but also cognitive processes, particularly the stability, capacity, distribution, and shifting of attention. The article analyzes the importance of sensorimotor exercises, methods for developing visual and auditory attention, games that activate speech-related attention, and speech therapy training. Practical recommendations are also provided for speech therapists and teachers.